The Invention of Sacred Places and Rituals A Comparative Study of Pilgrimage - Eade, John 1946- (2020)
During the last twenty years around the world there has been a rapid increase in the number of people visiting long established religious shrines as well as the creation of new sites by those operating outside the boundaries of institutional religion. This increase is intimately associated with the revival of traditional routes, the creation of new ones and the invention of new rituals (religious, spiritual and secular). To examine this process, I will focus on the European region and two contrasting destinations in particular—the Catholic shrine of Lourdes, France, and the pre-Christian shrine of Avebury, England—drawing on my personal involvement in travelling to both destinations and being involved in ritual activities along the route and at the two destinations. In the discussion section of the paper, I will explore the relevance of these two case studies to the analysis of power, agency and performance and the ways in which they expose (a) the role of institutions and entrepreneurs in creating rituals and sacred places and (b) the relationship between people and the domesticated landscape.
Keywords: Europe; Agency; Entrepreneurs; institutional religion; Landscape; Pilgrimage; Power; Ritual; Routes; sacred places